Economic and Policy Foundations for Growth in South East Europe - Bennett, A. author. aut Link
XIV, 139 p. 29 illus.
Keywords: This volume argues that a renewed commitment to sound macroeconomic policies and structural reforms is needed for countries in South East Europe, or 'the Balkans' achieve to sustainable prosperity, along with enhanced support from the international community. New fiscal and financial architecture has valuable lessons for policymakers in SEE.